Antihypercholesterolemic Activity of the Ethanol Extract Combination of Leaves Calotropis gigantea L. and Adenanthera pavonina L. - Galuh Anggun Oktaviani; Gaby Ayu Patricia; Cicik Wijayanti; Khoirul Ngibad (Justek : Jurnal Sains dan Teknologi, 2025)
Hypercholesterolemia is a significant risk factor for cardiovascular disease, and its prevalence continues to increase. Pharmacological therapy using statins is effective but may cause side effects when used long-term. Therefore, exploring natural ingredients as an alternative antihypercholesterolemic therapy is essential. This study aimed to evaluate the activity of a combination of ethanol extracts of Calotropis gigantea L. leaves and Adenanthera pavonina L. on the cholesterol levels of male mice induced with propylthiouracil (PTU). The study was conducted experimentally using a post-test-only control-group design with 36 male mice divided into six groups: negative control, positive control, drug control (simvastatin), and three treatment groups receiving extract combinations at doses of 14, 28, and 56 mg/g BW. The research stages included seven days of animal adaptation, induction of hypercholesterolemia with PTU for 14 days, administration of the extract combination at doses of 14, 28, and 56 mg/g BW for four days, and blood sampling for total cholesterol measurement using an automated chemical spectrophotometer. The results showed a significant increase in cholesterol levels in the positive control group, while simvastatin produced the most significant reduction. The extract combination gradually decreased cholesterol levels with increasing dose, with the highest dose approaching the effect of simvastatin. The paired t-test showed a p-value < 0.05, indicating significant differences between treatments. The combination of Calotropis gigantea L. and Adenanthera pavonina L. leaf extracts has potential as a herbal agent to support antihypercholesterolemic therapy.